Use of the Karelian language online: websites in Karelian: Karjalan kielen käyttö verkkosivujen kielenä - Moshnikov, Ilia (AFinLAn vuosikirja, 2022)
The use of the Karelian language on the internet has grown strongly over recent decades. The aim of this article is to analyze the visibility of the Karelian language on the internet, focusing on websites using Karelian as the language of the interface. The research data is analyzed comparatively from the perspective of positioning the Karelian language among other language versions. The study shows that the number of websites in Karelian has decreased since 2016. The use of different dialects of Karelian on websites varies. However, the visibility of the language in official contexts is rare, which could be explained by the lack of official status and the dearth of financial and human resources. This study describes existing resources in Karelian, but also shows the challenges of using Karelian and suggests developing strategies for making the Karelian language more accessible and visible on the internet. The use of the Karelian language on the internet has grown strongly over recent decades. The aim of this article is to analyze the visibility of the Karelian language on the internet, focusing on websites with a full interface in Karelian. The research data are analyzed comparatively from the perspective of the use of Karelian dialects on different websites. The study shows that the number of websites in Karelian is decreasing. The use of different dialects of Karelian on websites varies. The visibility of the language in official contexts is rare, which could be explained by the lack of official status and the dearth of financial and human resources. This study describes existing websites in Karelian, but also shows the challenges of using Karelian on the internet from a language ideology point of view and in terms of linguistic landscape theory.